Telaah Historis pada Manajemen Dakwah Siti Rajana Hasibuan di Kabupatem Padang Lawas Sumatera Utara - Daulay, Hamdan (Tadbir: Jurnal Manajemen Dakwah FDIK IAIN Padangsidimpuan, 2019)
With the extraordinary achievements in educating children and becomingan al Qur’an reciting teacher for a long time, the society gave her the title of anexemplary teacher to Siti Rajana Hasibuan, although she never received anycertificate from the government. From the gender perspective, she also deserves tobe called a woman public figure who has really proven herself that she is able toachieve an extraordinary achievement in religious teaching. Her relentless,persistent, and patient struggle in teaching her village children is entitled to be anexample for everybody. Indeed, gender does not have to follow the trend to fight forequality between men and women in politics and sports. Women can stand up as anexample in many other fields, including preaching and religious teaching. In herpreaching struggle, not everything goes smoothly. There were moments where shefaced obstacles and challenges in preaching as the juvenile delinquency increases.At the moment, Siti Rajana Hasibuan feels that the struggle to teach children inreading al Qur’an is immensely hard. The rapid growth of media makes childrenignore the study in al Qur’an reading, which makes her concerned about thegeneration which is al Qur’an illiterate when many children ignore religiousteaching.Keyword: Preaching Exemplary, Studying Al-Quran, Preaching ChallengesAbstrakKeberhasilan yang luar biasa dalam mendidik anak dan juga menjadi gurumengaji dalam waktu yang cukup lama, masyarakat memberi predikat guruteladan kepada Siti, walaupun ia tidak pernah menerima selembar sertifikat daripemerintah. Dari perspektif jender, ia juga pantas disebut sebagai tokoh wanitayang telah membuktikan diri secara nyata bahwa ia mampu mengukir prestasi yangluar biasa dalam bidang pendidikan agama. Perjuangannya yang gigih, ulet dansabar dalam mendidik anak-anak di desanya, pantas menjadi teladan bagi semuamasyarakat. Karena sesungguhnya jender tidak harus latah memperjuangkankesetaraan wanita dengan pria dalam bidang politik dan olah raga. Wanita bisatampil menjadi teladan dalam berbagai bidang, termasuk dalam bidang dakwah danpendidikan agama. Perjuangan dakwah Siti tentu tidak semua berjalan mulus, adasaatnya ia mengalami hambatan dan tantangan dakwah seiring dengan semakinbanyaknya kenakalan remaja. Saat ini Siti merasakan betapa berat perjuanganmendidik anak-anak dalam belajar membaca al Qur’an. Kehadiran media yangbegitu pesat membuat anak-anak semakin lalai dalam belajar membaca al Qur’an,sehingga membuat kekhawatiran Siti pada generasi yang buta huruf al Qur’anketika semakin banyak anak-anak yang lalai belajar agama.Kata Kunci: Dakwah, Tantangan.